Bioinspired nanoplatelets for chemo-photothermal therapy of breast cancer metastasis inhibition. (June 2019) - Ye, Hao; Wang, Kaiyuan; Wang, Menglin; Liu, Rongzheng; Song, Hang; Li, Na; Lu, Qi; Zhang, Wenjuan; Du, Yuqian; Yang, Wenqian; Zhong, Lu; Wang, Yu; et al.
Abstract: Breast cancer is associated with high mortality due to tumor metastasis. The anti-metastasis efficacy of photochemotherapy is strictly limited by poor targeting capability with respect to circulating tumor cells (CTCs) in blood and lymph. Herein, we decorate the platelet membrane (PM) on a surface of nanoparticles (NPs), referred to as nanoplatelets. A chemotherapeutic drug, doxorubicin (DOX), and an FDA-approved photothermal agent, indocyanine green (ICG), are co-encapsulated into the biomimetic nanoplatelets. Nanoplatelets possess immune surveillance-escaping capability and specifically capture and clear CTCs in both blood and lymphatic circulations via high-affinity interactions between the P-Selectin of PM and CD44 receptors of tumor cells. PM-coated NPs show greater cellular uptake in MDA-MB-231 breast cancer cells and further elicit higher cytotoxicity to tumor cells relative to uncoated NPs. In vivo, we disclose that the multifunctional nanoplatelets not only completely ablate the primary tumor but also inhibit breast cancer metastasis with high efficiency in the three established xenograft or orthotopic breast tumor-bearing mice models. We conclude that such biomimetic nanoplatelets represent a promising strategy of coating a surface of nanoparticles with platelet membrane to actively capture and destroy CTCs in blood and lymph in breast cancer anti-metastasis therapy.